Creep–fatigue interaction behavior of 316LN austenitic stainless steel with varying nitrogen content. (25th December 2015) - Prasad Reddy, G.V.; Sandhya, R.; Sankaran, S.; Parameswaran, P.; Laha, K.
Abstract: Creep–fatigue interaction (CFI) behavior of 316LN stainless steel with varying nitrogen content (0.07, 0.14 and 0.22 wt.%) is investigated at temperature of 873 K under strain-controlled fatigue tests with a tensile-hold period of 1, 13.3 and 30 min. Dynamic strain aging, thermal-recovery and/or dislocation–precipitate interactions are found to strongly control CFI deformation. At all the nitrogen contents in 316LN SS, the amount of stress relaxation and the associated relaxation strain rate decreased with increase in hold duration. Irrespective of the hold period, wavy-slip dislocation structures (cells, tangles, walls) are noticed at 0.07 wt.% N, whereas dislocation structures such as planar slip bands impinging on grain boundary are noticed, in addition, at nitrogen contents above 0.07 wt.%. Nitrogen content played a dual-role in influencing the CFI life. At 1-min hold where the failure is by transgranular plus intergranular fracture, increase in nitrogen from 0.07 to 0.14 wt.% caused an improvement in CFI life. On the other hand, CFI life decreased with increasing nitrogen content at 13.3 and 30-min hold durations that induced significant intergranular damage. Intergranular damage is evidenced in the form of triple point cracks and interconnected networks of grain boundary decohesion. Graphical abstract: Highlights: At all nitrogen contents, stress-relaxation decreases with increase in hold duration. Relaxation-strain rate decreases from 10 − 5 to 10 − 8 s − 1 with increasing hold period. At 1-min hold, increase in nitrogen to 0.14 wt.% improves creep–fatigue life. In CFI tests that induce intergranular damage, increasing nitrogen decreases life.